Can the Pessary Use Modify the Vaginal Microbiological Flora? A Cross-sectional Study - Suelene Costa de Albuquerque Coelho; Paulo César Giraldo; Juliana Oquendo Florentino; Edilson Benedito de Castro; Luiz Gustavo Oliveira Brito; Cássia Raquel Teatin Juliato (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Introduction Vaginal pessary is used as a conservative treatment for pelvic organ prolapse (POP). Some studies have shown that common complaints of its use may include vaginal discomfort and increased vaginal discharge. Scant information is available about the microflora status after using this device. Objective To determine if the usage of vaginal pessary can interfere with the vaginal environment. Methods A cross-sectional study was performed from March of 2014 to July of 2015 including 90 women with POP. The study group was composed of 45 women users of vaginal pessary and 45 nom-users. All enrolled women answered a standardized questionnaire and were subjected to a gynecological exam to collect vaginal samples for microbiological evaluation under optic microscopy. Clinical and microbiological data were compared between study and control groups. Results Vaginal discharge was confirmed in 84% of the study group versus 62.2% in the control group (p< 0.01); itching was reported in 20 and 2.2%, respectively (p< .05); genital ulcers were only found in the pessary group (20%). There was no difference with regard to the type of vaginal flora. Bacterial vaginosis was prevalent in the study group (31.1% study group versus 22.2% control group), (p=.34). Conclusion Women using vaginal pessaries for POP treatment presented more vaginal discharge, itching and genital ulcers than non-users.